Legal Certainty in Prosecutorial Indictments of Criminal Cases in Tanah Datar Regional Regent Election - Fery Ardiansyah; Yenny Fitri Z. (Yayasan Lembaga Studi Makwa, 2026)
This study aims to analyze legal certainty in prosecutorial indictments of criminal cases related to the Tanah Datar Regional Regent Election and to examine factors affecting the consistency of electoral criminal law enforcement within regional democratic processes in Indonesia. The research employed a qualitative juridical approach with a case study design. Data were collected through the analysis of prosecutorial indictments, electoral regulations, court decisions, and interviews with legal actors involved in electoral criminal law enforcement. The findings reveal that prosecutorial indictments were generally formulated in accordance with Indonesian criminal procedural law and electoral regulations by incorporating factual evidence, witness testimonies, and reports from election supervisory institutions. Such formulation contributes to legal certainty in the prosecution process by ensuring that criminal charges are based on clear legal grounds and evidentiary standards. However, several factors affecting legal certainty were identified, including limited institutional coordination, difficulties in obtaining reliable evidence, inconsistencies in legal interpretation, and political pressures during regional elections. The study further demonstrates that legal certainty in prosecutorial indictments plays an important role in ensuring fairness, consistency, and accountability in handling electoral criminal cases. Prosecutorial indictments function not only as procedural legal instruments but also as mechanisms for maintaining democratic integrity and public trust in electoral processes. The study concludes that strengthening legal certainty in prosecutorial indictments significantly influences the quality of electoral justice and democratic accountability in regional elections and contributes to the development of electoral criminal law studies in Indonesia.